Contribution to portuguese urban fire investigations: forensic fire debris analysis - Oliverio, Stefania (2016)
Fire scene investigation and fire debris analysis (FDA) are two tightly linked and mutually exclusive key elements of a forensic arson investigation. While the fire scene investigation is performed by a trained fire investigator, FDA is a task undertaken by a fire debris analyst, which is normally a forensic chemist with expert knowledge in analytical chemistry. To solve a case efficiently and successfully, cooperation and information- and knowledge-exchange are necessary, especially since this branch of forensic science is defined as one of the most complex and arduous ones due to the highly destructive nature of fires that severely compromises the integrity of the evidence collected at the crime scene. The task of analysing the fire debris for the detection of ignitable liquid residues (ILRs) is further complicated by the large influence and existence of interfering products. Most ignitable liquids (ILs) are made of hydrocarbons, which are also compounds that have been found in the substrate of common household or construction materials as well as being created during the processes of combustion and pyrolysis. The purpose of this study was to identify and characterize background, combustion and pyrolysis products of commonly encountered substrate materials in fire scenes in Portugal and observe the effects on ILRs identification by using headspace solid-phase micro-extraction linked to gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results show that both the background of the substrates and the combustion and pyrolysis products formed during a fire include many compounds that constitute common ILs, such as alkanes and aromatics, that especially in the presence of low amount of ILRs constitute a problem in the conclusive identification of ILs. Even though detailed analysis of the chromatographic and mass-spectral patterns and the combinations of compounds detected in the materials can avoid misinterpretation, in some cases, awareness and knowledge of interfering products is essential.